PERBEDAAN RERATA FAKTOR HEMOSTASIS PADA PREEKLAMPSIA BERAT DAN EKLAMPSIA - Dyhan Purna Setia; Ferdinal Ferry; Dovy Djanas (Andalas Obstetrics And Gynecology Journal, 2019)
Objective : To find the difference in mean hemostatic factors in severe preeclampsia and eclampsia.Method : The study was analytic descriptive using a cross sectional study design by looking at the subject's Medical Record according to the time and place of research. The sample is the entire medical record of pregnant women who suffer from preeclampsia and eclampsia in the obstetric and gynecology departments of Dr. M. Djamil Padang Hospital in the period 15 January 2016 to 31 December 2017. The assessment was in the form of assessed platelet levels, PT, APTT and D-Dimer. Samples were taken from populations that met the inclusion criteria and did not have exclusion criteria. Sampling using consecutive sampling techniques taken from the Medical Record Dr. M.Djamil Padang. Statistical analysis to assess significance using the T-Test.Result : The severity the condition of pregnancy the lower the platelet mean and PT. Significant differences were obtained between platelets in PEB and eclampsia (p> 0.05). The mean PT, APTT and D-Dimer showed no significant differences in pregnancy conditions. Statistical test with T-Test did not show significant differences in mean PT, APTT, and D-dimer between eclampsia and PEB (p> 0.05).Conclusion : There were significant differences in mean in platelets, whereas in PT, APTT, and D-dimers in PEB and eclampsia there were no significant differences.Keywords: Pregnancy, severe preeclampsia, eclampsia, platelets, PT, APTT, D-Dimer.